2021
DOI: 10.3389/fninf.2020.575999
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Methods for Diagnosing Autism Spectrum Disorder and Attention- Deficit/Hyperactivity Disorder Using Functional and Structural MRI: A Survey

Abstract: Here we summarize recent progress in machine learning model for diagnosis of Autism Spectrum Disorder (ASD) and Attention-deficit/Hyperactivity Disorder (ADHD). We outline and describe the machine-learning, especially deep-learning, techniques that are suitable for addressing research questions in this domain, pitfalls of the available methods, as well as future directions for the field. We envision a future where the diagnosis of ASD, ADHD, and other mental disorders is accomplished, and quantified using imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 176 publications
(196 reference statements)
0
57
0
Order By: Relevance
“…Prior studies using smaller samples did not use independent tests sets (Eslami et al, 2021;Wolfers et al, 2019), which may have led to overly optimistic estimates of accuracy (Brain & Webb, 1999;Wolfers et al, 2015). Indeed, studies with very small sample sizes (<300 training samples) often reported higher accuracies with a wide range of variability (e.g., 68%-99% as reviewed by Eslami et al (2021) than those that used larger samples sizes (e.g., sample sizes ranging from 650 to 906 in Demirhan (2018), Haar et al (2016), andKatuwal et al (2015). None of the above studies with larger sample sizes reported classification accuracies higher than 60% even with using various forms of cross-validation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies using smaller samples did not use independent tests sets (Eslami et al, 2021;Wolfers et al, 2019), which may have led to overly optimistic estimates of accuracy (Brain & Webb, 1999;Wolfers et al, 2015). Indeed, studies with very small sample sizes (<300 training samples) often reported higher accuracies with a wide range of variability (e.g., 68%-99% as reviewed by Eslami et al (2021) than those that used larger samples sizes (e.g., sample sizes ranging from 650 to 906 in Demirhan (2018), Haar et al (2016), andKatuwal et al (2015). None of the above studies with larger sample sizes reported classification accuracies higher than 60% even with using various forms of cross-validation.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed xAI-EWS method potentially executes medical translation by attaining an estimation with EHR data and its description. Eslami et al [12] summarized the current developments in ML model for the diagnoses of ASD and ADHD. The researchers described and outlined the ML approach, particularly DL methods that are relevant to the area of research in these domains, drawbacks of the access methods, and upcoming directions for the domain.…”
Section: Literature Surveymentioning
confidence: 99%
“…The risk of worsening symptomatology can be predicted by using machine learning models, which have proved valuable in the field of psychiatry ( Bzdok and Meyer-Lindenberg, 2018 ; Dwyer et al, 2018 ; Janssen et al, 2018 ; Xu et al, 2019 ; Eslami et al, 2021 ) for predicting the appearance of symptoms and changes in the prognosis of some disorders such as depression, anxiety and psychosis, with the aim of providing appropriate psychological and/or pharmacological treatments. Machine learning has also proved useful for predicting changes in symptomatology in OCD patients over time ( Hoexter et al, 2013 ; Agne et al, 2020 ) and for predicting the severity of OCD symptoms in combination with other methods ( Hoexter et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%